Rhodium(I)-Catalyzed Enantioselective Cyclization of Enynes through Site-Selective C(sp3)–H Bond Activation Triggered by Formation of Rhodacycle - Oonishi, Yoshihiro; Sakamoto, Shunki; Agata, Shuya; Sato, Yoshihiro (Synthesis, 2021)
Rhodium(I)-catalyzed enantioselective cyclization of enynes through C(sp3)–H bond activation was investigated. It was found that the cyclization of enynes having a tert-butyl moiety on the alkene afforded a spirocyclic compound (up to 92% ee), while the cyclization of enynes having an isopropyl or an ethyl group on the alkene gave a cyclic diene (up to 98% ee). Furthermore, an intermolecular competition reaction using a deuterium-labeled substrate revealed that C(sp3)–H bond activation was one of the key steps, having a high energy barrier, in this cyclization.
Keywords: rhodium; enantioselective cyclization; C(sp3)–H bond activation; alkene; alkyne; enyne